Evaluasi Pengalaman Pengguna Aplikasi SIMARIS UPN “Veteran” Jawa Timur Menggunakan Metode UEQ - Anisa Rahma Salsabila; Tri Lathif Mardi Suryanto; Eristya Maya Safitri (JURIKOM (Jurnal Riset Komputer), 2022)
The implementation of information and communication technology in a university is increasing according to the needs of each university. Research and community service activity carried out by lecturers at UPN "Veteran" East Java have been accommodated by an application called SIMARIS. In its implementation, this application still has several complaints related to the user experience felt by lecturers, such as difficulties when viewing proposal details, limitations for uploading files, no preview feature to view files, and the reviewer assessment menu doesn’t work for lecturers. In this study, the user experience of SIMARIS application was evaluated using the User Experience Questionnaire (UEQ) method. The questionnaire data obtained will be analyzed using UEQ Data Analysis Tool. The measurement results show that each scale has a high mean value with the scale of Attractiveness 1.61, Perspicuity 1.52, Efficiency 1.64, Dependability 1.44, Stimulation 1.51, and Novelty 1.25. The consistency level of all scales shows that Cronbach's Alpha value > 0.70. This means a high level of consistency is owned by all scales.